Rebuilding Identity After a Natural or Human Generated Disaster - Ann Brooks; Moira Martin; Michelle Holcomb (Adult Education Research Conference, 2018)
How do disaster survivors make sense of their lives? Drawing on three studies, we use the concepts of extended and relational self to understand how disaster survivors reconstruct their identities.
Keywords: natural disasters; survivors; identity